Non-Wilms' renal tumors in children: experience with 139 cases treated at a single center - Yi Wei Fang; Hong Cheng Song; Ning Sun; Wei Ping Zhang (BMC Urology, 2022)
Abstract Background Pediatric non-Wilms renal tumors (NWRTs), which comprise a small proportion of renal tumors, are a heterogeneous group of neoplasms with variable malignant potential, mortality, and response to treatment. We performed this study to determine the clinical characteristics, management and prognosis of children with Pediatric NWRTs. Methods Medical records of all patients (n = 139) treated for NWRTs over a 12-year period (2008.01–2019.10) at a single center were reviewed retrospectively. Results The histopathological groups of NWRTs included malignant rhabdoid tumor of the kidney (MRTK) (n: 30, 21.6%), renal cell cancer (RCC) (n: 26,18.7%), clear cell sarcoma of the kidney (CCSK) (n: 24,17.3%), congenital mesoblastic nephroma (CMN) (n: 21,15.1%), cystic nephroma (CN) (n: 16,11.5%), metanephric tumors (n: 12, 8.6%), renal angiomyoliporma (RAML) (n: 3, 2.2%), renal primitive neuroectodermal tumor (n: 2, 1.4%), renal hemangioma (n: 2, 1.4%), inflammatory myofibroblastic tumor (n: 2, 1.4%), ossifying renal tumor of infancy (ORTI) (n: 1, 0.7%). The distribution of all malignant NWRTs, including MRTK, CCSK, RCC and PNET, according to stage was as follows: stages I (n = 26), II (n = 16), III (n = 29), and IV (n = 11). The summary table shows the treatment offered to children with NWRTs. A total of 123 children were followed up for an average of 42 months. Sixteen children were lost to follow-up. Tumor-free survival was observed in 94 children. One patient who suffered from RCC is currently receiving targeted therapy and survives with the tumor. Twenty-eight children (22.8%) died. Conclusions Pediatric NWRTs comprise 19.1% of all renal tumors in our single center. Most NWRTs can readily be distinguished using a range of immunohistochemical markers. Molecular genetic profiling has allowed much progress in the understanding of this group of tumors, making diagnosis and classification less difficult. The mainstay treatment of malignant NWRTs, including MRTK, CCSK, RCC and PNET, is comprehensive treatment. The mainstay treatment of benign NWRTs, including RAML, CN, ORTI, CMN, metanephric tumors, and renal hemangioma, is surgical resection alone and when the tumor diameter is smaller than 7 cm and the tumor locates in one pole, NSS can be performed.